Gene dosage compensation of rRNA transcript levels in Arabidopsis thaliana lines with reduced ribosomal gene copy number. Issue 4 (2nd February 2021) - Lopez, Francesca B; Fort, Antoine; Tadini, Luca; Probst, Aline V; McHale, Marcus; Friel, James; Ryder, Peter; Pontvianne, Frdric; Pesaresi, Paolo; Sulpice, Ronan; McKeown, Peter; Brychkova, Galina; et al.
Abstract: The 45S rRNA genes (rDNA) are among the largest repetitive elements in eukaryotic genomes. rDNA consists of tandem arrays of rRNA genes, many of which are transcriptionally silenced. Silent rDNA repeats may act as 'back-up' copies for ribosome biogenesis and have nuclear organization roles. Through Cas9-mediated genome editing in the Arabidopsis thaliana female gametophyte, we reduced 45S rDNA copy number (CN) to a plateau of ∼10%. Two independent lines had rDNA CNs reduced by up to 90% at the T7 generation, named low copy number (LCN) lines. Despite drastic reduction of rDNA copies, rRNA transcriptional rates, and steady-state levels remained the same as wild-type plants. Gene dosage compensation of rRNA transcript levels was associated with reduction of silencing histone marks at rDNA loci and altered Nucleolar Organiser Region 2 organization. Although overall genome integrity of LCN lines appears unaffected, a chromosome segmental duplication occurred in one of the lines. Transcriptome analysis of LCN seedlings identified several shared dysregulated genes and pathways in both independent lines. Cas9 genome editing of rRNA repeats to generate LCN lines provides a powerful technique to elucidate rDNA dosage compensation mechanisms and impacts of low rDNA CN on genome stability, development, and cellular processes. Abstract : Ribosomal gene reduction does not affect rRNA homeostasis but is correlated with loss of enrichment of heterochromatic marks, signs of genome instability and dysregulated metabolic pathways.